Visual archives in digital newspapers: an aproach to visual lexicon in an information visualization prototype - Fernandes, Marta (2022)
By rethinking how digital information and media have evolved, we intend to discuss how Information Visualization is performing an essential role in the field of newspapers, and how it can evolve with particular emphasis on content archiving for future access. The presence of new visual structures used in fields such as digital archiving, have questioned digital methods of preservation and how the interrelation between information and access to knowledge is revealed. In digital newspapers, the development of access and information retrieval processes has become an essential part of their duties, but it is still in it’s infancy and dependent on text search rather then content awareness. By outlining the links between Visual Archives and Information Visualization, with focus on online press, we venture in a path of trial and error. This is present by the recognition of lack of efficient articulation between different types of contents, as well as between the user interaction and the contents outcomes. Thus proposing a visual lexicon that can adjust to the constraints of technology, different user devices, and the promptitude of publication that a Web context demands it is utmost relevant. A combination of fields, with attention to visual perception and arbitrary conventions in relation to image and content awareness, grants the association of concepts such as big data and thick data description, being part of the outcomes of this research a proposal to a theoretical model grounded on prototyping testing in a newsroom office.      This empirical methodological approach is supported by a low-fidelity prototype, for iterative formative evaluations, fostering field’s observations with potential users in order to identify the best visual components of a digital visual archive for online newspapers. The challenge is to develop visual structures that preserve and present the interconnections of news, information and knowledge to be seen, accessed and linked. By making use of a lo-fi prototype of a visual digital archive we aimed, to test, re-test, and find responses in dialogue, failure and retrial. The body of work shown here presents the practical outcomes of the theoretical model.